5G-Driven Improvements in IoT Networks: An Analytical Study of Technological Applications in Smart Environments - Ahmed Elstial; Talal Mohammed; Salma Albahlul (المجلة الأفروآسيوية للبحث العلمي, 2025)
The explosively increasing number of Internet of Things (IoT) objects in smart environments has driven the appearance of several challenges concerning network efficiency, latency and energy control. In this paper, a framework where 5G wireless technology along with edge computing and AI is used to improve the performance of IoT networks is proposed. Simulation results in MATLAB are experienced to demonstrate the performance of AI-based optimization techniques for dynamic 5G-IoT scenarios. Compared to traditional centralized approaches, this paper experimentally shows that the proposed model achieves significant increase in network efficiency by 35.2%, latency reduction by 42.1% and energy saving of 28.4%. With its ability to integrate AI-based optimization into 5G-enabled IoT networks, the suggested framework provides a scalable and energy-efficient solution for smart environments of the future.